RAGAM BERBAGAI PERBENIHAN BAKTERI TERKAIT KERENTANANNYA TERHADAP ANEKA JENIS ANTIBIOTIKA - Carolina M Viany S; Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Infection is the major public health problem in Indonesia which could increase its morbidity and mortality. The antibiotics treatmentwhich were given irrationally leads to bacteria susceptibility and worsen the problem. One of the efforts to manage the bacteriasusceptibility the physician has to know the bacterial pattern and its characteristic to resist various antibiotics. The information maycontribute as a reference to give antibiotic therapy in a rational manner. To know the bacterial susceptibility pattern against variousantibiotics a study was carried out using specimens derived from several hospitals which referred them to a private laboratory inSurabaya. The specimens consisted of blood, urine and sputum were referred during September 2007 up to July 2008. The identificationof the bacteria and it‘s susceptibility pattern were carried out by a conventional method and an auto analyzer (Vitek 2 Compact). Theantibiotic susceptibility test was carried out by conventional method using Kirby Bauer modifiied diffusion technique and Vitec 2 Compactusing MIC reference. The results showed that the most common bacteria found from blood was Escherichia coli which was still sensitiveto amoxicillin-clavulanic acid, amikacin, and cefepim. And from the urine was Escherichia coli which were still sensitive to meropenemfollowed by amikacin and gentamycin. Whereas from the sputum was found Streptococcus α haemolyticus which was still sensitive toamoxicillin-clavulanic acid, piperacillin tazobactam, linezolid. The result of the antibiotic susceptibility test is mostly dominated bythe Betalactam group, such as amoxicillin-clavulanic acid and carbapenem group like meropenem. Besides of that, in this study wasalso found multiple drug resistance organisms (MDRO), such as Escherichia coli ESBL, Enterobacter liquefaciens ESBL, Enterobacteragglomerans ESBL, Klebsiella ozaenae ESBL, and Klebsiella pneumoniae ESBL. The susceptibility pattern of the bacteria derived fromblood and sputum is dominated by gram positive cocci. Whereas from urine is dominated by Gram negative rods.